The neuroregenerative mechanism mediated by the Hsp90-binding immunophilin FKBP52 resembles the early steps of neuronal differentiation - Quintá, Héctor Ramiro (2012)
BACKGROUND AND PURPOSE The immunosuppressive macrolide FK506 (tacrolimus) shows neuroregenerative action by a mechanism that appears to involve the Hsp90-binding immunophilin FKBP52. This study analyses some aspects of the early steps of neuronal differentiation and neuroregeneration. EXPERIMENTAL APPROACH Undifferentiated murine neuroblastoma cells and hippocampal neurones isolated from embryonic day-17 rat embryos were induced to differentiate with FK506. Subcellular relocalization of FKBP52, Hsp90 and its co-chaperone p23 was analysed by indirect immunofluorescence confocal microscopy and by Western blots of axonal fractions isolated from cells grown on a porous transwell cell culture chamber. Neuroregeneration was evaluated using a scratch-wound assay. KEY RESULTS In undifferentiated cells, FKBP52, Hsp90 and p23 are located in the cell nucleus, forming an annular structure that disassembles when the differentiation process is triggered by FK506. This was observed in the N2a cell line and in hippocampal neurones. More importantly, the annular structure of chaperones is reassembled after damaging the neurones, whereas FK506 prompts their rapid regeneration, a process linked to the subcellular redistribution of the heterocomplex. CONCLUSIONS AND IMPLICATIONS There is a direct relationship between the disassembly of the chaperone complex and the progression of neuronal differentiation upon stimulation with the immunophilin ligand FK506. Both neuronal differentiation and neuroregeneration appear to be mechanistically linked, so the elucidation of one mechanism may lead to unravel the properties of the other. This study also implies that the discovery of FK506 derivatives, devoid of immunosuppressive action, would be therapeutically significant for neurotrophic use.